(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Agricultural waste management remains a critical aspect of sustainable agriculture in Caraga Region, Philippines. Agricultural waste is generally not reused or recycled for economic purposes and for reducing gas emissions due to lack of institutional and technical support. This study aims to develop a circular economy (CE) framework reflecting the local realities to guide the management of common agricultural waste. Using qualitative research design, data were gathered from 41 respondents through key informant interviews, 100 stakeholders in the focus group discussions, and documents from secondary sources. Using NVivo, the study revealed that common agricultural wastes come from rice farming, corn farming, coconut plantation, banana plantation and from livestock and poultry. These wastes are predominantly managed through informal and not environmentally friendly practices, including open burning and dumping. Key challenges include limited policy support, lack of appropriate technologies, and weak institutional coordination. Nevertheless, opportunities for waste valorization abound in Caraga Region, including reuse into mushroom beds, composting for organic agriculture, and biochar production. From the findings, the proposed CE framework will encompass waste characterization, stakeholder collaboration, policy and institutional support, technology and innovation, and capacity building for the key actors, the rural women. The framework supports a strategic approach to transition to sustainable agricultural waste management in Caraga Region through circularization, with potential applications in the entire Philippines.